All-on-four treatment in implantology: concept and updates (Research, Society and Development, 2020)
Introduction: Rehabilitation through the "all-on-four" treatment maximizes the use of the remaining bone available in atrophic jaws. Objectives: To analyze the concept of all-on-four treatment and its updates, based on surgical and prosthetic topics. Methodology: A review of the literature was carried out through the search for scientific articles of the last 10 years, in the Pubmed database. Data were analyzed descriptively. Results: The studies revealed a survival rate of 98.9%, implant angles ranging from 30 to 45 degrees. This technique allows maximum use of the remaining bone structure and avoids regenerative procedures to the patient and is favorable in terms of quality of life. Conclusion: The all-on-four treatment in Implantology consists of an innovative and effective technique with predictability, with a high success rate in edentulous jaws.